Multicultural philosophy and education for civic coexistence (2013)
Current societies tend to be more open, pluralistic, and multicultural as a consequence of a globalized world that affects in different ways individuals and communities’ lifestyles. However, along with the idea of global village, there arise some local, personal, and group reactions that claim nationalist feelings as well as beliefs, cultural bonds, and collective identities, creating conflict situations, intolerance, and non-acceptance of differences. In this context, it happens to be more useful for social life to educate new generations based on criteria to live together in multicultural and pluralistic environments than to root out prejudices, violence and marginalization arising from intolerable and exclusive ways of thinking. Therefore, teaching of philosophy keeps valid as a reflection school space where it is possible to discuss, formulate, and assume points of views ethically sustainable and rationally justified that contribute to strengthen a peaceful, democratic and respectful-of-human-dignity civic coexistence